The financing of young firms. How persistent are borrowing constraints? - Erik Fjærli; Diana Iancu (Statistics Norway, Research Department, 2012)
Are investments by new firms constrained by access to financing? If so, are the constraints persistent or do firms overcome their financing problems during the first years of operation? We examine the role of capital constraints by estimating the relation between founders' initial wealth and firm size during the first years of operation. Similar to previous studies, we find a positive impact of entrepreneurs' wealth prior to start-up on the start-up size of entrepreneurial firms, but this effect decreases during the first five years of operation. We also document a high degree of economic mobility among entrepreneurial firms during the first years of operation. This is primarily driven by a disproportional increase in debt financing among the smallest firms, indicating that capital constraints for entrepreneurs are transitory.
Keywords: L11; 330; Entrepreneurship; borrowing constraints; growth